Masalah Pelestarian Jalak Bali - Hadi S Alikodra (Media Konservasi, 1987)
Lhuing the times of the census 1974 - 1981 the Bali mynah population steadily increased, but from 1983 - 1986 it has steadily decreased. At present the population of the Bali mynah is declining at an alarming rate, so it needs a realistic conservation programme designed to enhance the survival of this species. The population decline is related to the environmental resistance, such as : illegal hunting, forest fine, and habitat destruction due to human pressure.